Pemanfaatan Pekarangan Rumah Tangga Melalui Teknik Vertikultur untuk Meningkatkan Kesejahteraan Keluarga - Afrianti, Suratni; Pinem, Laura Juita; Khairani, Siti (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to empower housewives living near the railway tracks in Sei Agul, Medan Barat, through vertical farming techniques. The program is designed to optimize the use of limited yard space around their homes to improve family income and community welfare. The methods used include training, mentoring, and periodic evaluations. The questionnaire instrument was distributed before and after the activity to determine the level of change in knowledge and skills received by participants during the activity. The results of the community service showed an increase in participants' knowledge and skills in farming using vertical farming techniques, packaging harvests, and marketing products both directly and digitally. In addition to providing economic benefits, this activity also supports environmental sustainability by reducing the use of land, water, and pesticides.